CLIMATE MOBILITY AND THE EMERGING LEGAL PROTECTION GAP: REASSESSING INTERNATIONAL REFUGEE LAW THROUGH A HUMAN SECURITY LENS - Anmol (Policy Journal of Social Science Review, 2025)
Climate change has become one of the greatest forces of human mobility in the twenty-first century, forcing millions of people to move as a result of sudden-onset disasters and slow-onset environmental changes like sea-level rise, desertification, drought, and coastal erosion. Although the number of climate-induced migrants is increasing, they are not recognized as refugees under the existing international refugee law, including the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol, which does not mention climate-induced migrants as refugees. This legal restriction has left millions of people without sufficient international legal protection. This paper critically reflects on how well the existing refugee protection framework is able to respond to climate mobility and considers the potential of the Human Security framework as an alternative refugee protection approach for climate displaced persons. The study uses a qualitative doctrinal research methodology and examines international legal instruments, UN reports, academic literature and selected case studies such as Pakistan, Bangladesh, Kiribati and Tuvalu. The results show that the current refugee framework is not sufficient to address the current trends of climate-induced displacement and that a human security approach offers a more comprehensive and people-centred understanding of protection, focusing on environmental, economic, food, health and personal security. The study calls for further strengthening of international legal instruments by improving cooperation, creating complementary protection instruments and embedding human rights principles in climate governance. It argues that a human security approach to international refugee law is needed to reflect the changing nature of climate mobility and to provide adequate legal protection for those impacted by climate change in today's rapidly changing climate. Keywords: Climate Mobility, Climate Change, Climate-Induced Displacement, International Refugee Law, Human Security, Climate Refugees, Environmental Migration. https://doi.org/10.5281/zenodo.21802263